Analisis Pembentukkan Portofolio Optimal Saham Menggunakan Pendekatan Single Index Model - M. Fathan Amin; Novi Mubyarto; Erwin Saputra Siregar (EBISMAN eBisnis Manajemen, 2024)
The capital market is an activity involving the trading of securities and public offerings. It also involves institutions and professions dealing with securities. Investors have the potential to allocate their funds to safe-haven investment instruments, although the increase in the number of investors does not correspond to the level of literacy, especially in the capital market, which was only 4.92% in 2019 and decreased to 4.11% in 2022. This research aims to determine how the optimal stock portfolio is formed on the IDX Shariah Growth index in the period from November 2022 to March and from April to August 2023. The research results show that in the period from November 2022 to March 2023, six stocks were selected as candidates for the optimal portfolio, including SMDR, PWON, ISAT, TINS, HEAL, and INCO. On the other hand, in the period from April to August 2023, only SMDR and MAPI were included as candidates. Interestingly, SMDR was consistently selected in both periods. The proportion of the optimal portfolio in November 2022 - March 2023 was 11.62% for SMDR, while in April - August 2023, the proportion of SMDR increased to 25%. The optimal portfolio consisting of two stocks in April - August 2023 is estimated to generate a return of -0,28% per month, with an investment risk of 2.25%. Compared to the period of November 2022 - March 2023, which resulted in a return not significantly different, namely -0,078%, the investment risk level was much higher at 3,8%. However, this risk is lower than investing in individual stocks. Thus, forming an optimal portfolio is one effective way to diversify and reduce investment risk.